Digital Watermarking Based on Contourlet-SVD - Seyedeh Akram Hosseini; Sedigheh Ghofrani (Majlesi Journal of Electrical Engineering)
in this paper, embedding a watermark image is performed in discrete Contourlet transform (CT) domain. It is known that the CT is able to capture the directional edges and contours superior to discrete wavelet transform. The proposed scheme is based on embedding watermark bits into the singular value of the selected blocks within low-pass sub-band of the original gray image CT. Two algorithms, the first uses adaptive quantization and the second uses quantization step, are implemented. Our experimental results show that the method with quantization step has better fidelity in terms of peak signal to noise ratio (PSNR) and is more robust against geometrical and non-geometrical attacks in terms of normalized cross correlation (NC) in comparison with the first method, though, the method with adaptive quantization is blind in the sense only quantization strategies but not the original image is required. Ø§ÙØ±ÙÙÛ Ø¨Ø§ÙÙØ§Ø¡ ÙØ¨ÙÛ Ø¹ÙÙ CONTOURLET-SVDÙÛ ÙØ°Ù Ø§ÙÙØ±ÙØ©Ø ÙØªØ¶ÙÛÙ ØµÙØ±Ø© ÙØ§Ø¦ÛØ© ÛØªÙ ØªÙÙÛØ°ÙØ§ ÙÛ ÙÙÙØµÙØ© Contourlet ØªØÙÛÙ (CT) Ø§ÙÙØ¬Ø§Ù. ÙÙÙ Ø§ÙÙØ¹Ø±ÙÙ Ø£Ù CT ÙØ§Ø¯Ø±Ø© Ø¹ÙÙ Ø§ÙØªÙØ§Ø· ØÙØ§Ù ÙÙØ¹Ø§ÙÙ Ø§ÙØ§ØªØ¬Ø§Ù ÙØªÙÙÙØ© Ø¹ÙÙ ÙÙÙØµÙØ© ØªØÙÛÙ Ø§ÙÙÙÛØ¬Ø§Øª. ÙÛØ³ØªÙØ¯ Ø§ÙÙØ®Ø·Ø· Ø§ÙÙÙØªØ±Ø Ø¹ÙÙ ØªØ¶ÙÛÙ Ø¨Øª Ø§ÙØ¹ÙØ§ÙØ© Ø§ÙÙØ§Ø¦ÛØ© Ø¥ÙÙ ÙÛÙØ© ÙØ±ÛØ¯Ø© ÙÙ Ø§ÙÙØ·Ø¹ Ø§ÙÙØ®ØªØ§Ø±Ø© Ø¶ÙÙ ØªÙØ±ÛØ± ÙÙØ®ÙØ¶ Ø§ÙÙØ±Ø¹ÛØ© Ø§ÙÙØ±ÙØ© ÙÙØ§ÙØ£ØµÙÛ Ø±ÙØ§Ø¯Û ØµÙØ±Ø© CT. Ø§Ø«ÙÛÙ ÙÙ Ø§ÙØ®ÙØ§Ø±Ø²ÙÛØ§ØªØ Ø£ÙÙ ØªØ³ØªØ®Ø¯Ù ØªÚ©ÙÛÙ Ø§ÙØªÚ©ÛÙ ÙÛØ³ØªØ®Ø¯Ù Ø«Ø§ÙÛ Ø®Ø·ÙØ© ØªÚ©ÙÛÙØ ÛØªÙ ØªÙÙÛØ°ÙØ§. ØªØ¸ÙØ± ÙÙØ§ Ø§ÙÙØªØ§Ø¦Ø¬ Ø§ÙØªØ¬Ø±ÛØ¨ÛØ© Ø£Ù Ø§ÙØ£Ø³ÙÙØ¨ ÙØ¹ Ø®Ø·ÙØ© ØªÚ©ÙÛÙ Ø¯ÛÙ Ø§ÙØ¥Ø®ÙØ§Øµ Ø£ÙØ¶Ù ÙÙ ØÛØ« Ø§ÙØ°Ø±ÙØ© Ø¥Ø´Ø§Ø±Ø© Ø¥ÙÙ ÙØ³Ø¨Ø© Ø§ÙØ¶ÙØ¶Ø§Ø¡ (PSNR) ÙØ£Ú©Ø«Ø± ÙÙØ© Ø¶Ø¯ Ø§ÙÙØ¬ÙØ§Øª ÙÙØ¯Ø³ÛØ© ÙØºÛØ± ÙÙØ¯Ø³ÛØ© ÙÙ ØÛØ« Ø¹Ø¨Ø± Ø¹ÙØ§ÙØ© Ø·Ø¨ÛØ¹ÛØ© (NC) ÙÙØ§Ø±ÙØ© ÙØ¹ Ø§ÙØ·Ø±ÛÙØ© Ø§ÙØ£ÙÙÙ Ø Ø¹ÙÙ Ø§ÙØ±ØºÙ ÙÙ Ø§ÙØ£Ø³ÙÙØ¨ ÙØ¹ ØªÚ©ÙÛÙ Ø§ÙØªÚ©ÛÙ Ø£Ø¹ÙÙ Ø¨Ø§ÙÙØ¹ÙÙ Ø§Ø³ØªØ±Ø§ØªÛØ¬ÛØ§Øª ØªÚ©ÙÛÙ ÙÙØ· ÙÙÚ©Ù ÙÛØ³ ÙØ·ÙÙØ¨Ø§ Ø§ÙØµÙØ±Ø© Ø§ÙØ£ØµÙÛØ©. æ°åæ°´å°åºäºè½®å»-SVD æ½è±¡ å¨æ¬æä¸ï¼ææ°´å°åµå¥å¾è±¡ä¸çç¦»æ£è½®å»æ³¢åæ¢ï¼CTï¼çåä¸æ§è¡ãä¼æå¨ç¥ï¼å¨CTè½å¤æè·æ¹åæ§è¾¹ç¼åè½®å»ä¼äºç¦»æ£å°æ³¢åæ¢ãææåºçæ¹æ¡æ¯åºäºæ°´å°æ¯ç¹åµå¥å°æéæ©çåçåå§ç°åº¦å¾åçCTä½éåå¸¦åçå¥å¼å¼ãä¸¤ç§ç®æ³ä¸ï¼é¦åä½¿ç¨èªéåºéååç¬¬äºä¸ªä½¿ç¨çéåæ¥é¿ï¼æ¥å®ç°ãæä»¬çå®éªç»æè¡¨æï¼ä¸éåæ¥é¿ï¼è¯¥æ¹æ³å·ææ´å¥½çä¿çåº¦å¨å³°å¼ä¿¡å·æ¡æ¬¾åªå£°æ¯ï¼PSNRï¼åå¨ä¸ç¬¬ä¸ç§æ¹æ³æ¯è¾æ¯éå¯¹å¨å½ä¸åäºç¸å³ï¼NCï¼èè¨å ä½åéå ä½æ»å»æ´å¥å£®ä¸è¿ï¼ä¸èªéåºéåçæ¹æ³æ¯å¨è¿ä¸ªæä¹ä¸åªéåçç¥ç²ä½å¹¶ä¸éè¦åå§å¾åã